A Century of Progress in Transportation
This photograph shows a Century of Progress in transportation - the famous old John Bull engine contrasted with one of the new Boeing monoplanes in service on United Air Lines' Coast-to-Coast and other routes. This three-mile-a-minute plane is the world's fastest multi-motored passenger-mail-express transport. It can fly nearly 150 miles an hour faster than the train drawn by the old type engines. The United Air Lines' plane was selected for exhibition in the Dome of the Travel and Transport Building because it represents latest features of airplanes design construction. Powered with two 550 h.p. supercharged Wasp engines, these Boeing Monoplanes can cruise 171 m.p.h. They land at the low speed of 59 miles per hour and take off after a run of only 770 feet. They can climb 1320 feet a minute at sea level and to 10,000 feet in eleven minutes. Carrying a full load of ten passengers, two pilots, stewardess, baggage, mail and express, these planes can climb with only one of their two engines if necessary.